Cessation of non-vitamin K antagonist oral anticoagulants in patients with atrial fibrillation. Issue 12 (16th October 2020) - Middeldorp, Melissa E; Gupta, Aashray; Elliott, Adrian; Kadhim, Kadhim; Thiyagarajah, Anand; Gallagher, Celine; Hendriks, Jeroen; Linz, Dominik; Emami, Mehrdad; Mahajan, Rajiv; Lau, Dennis; Sanders, Prashanthan
Abstract : Objective: To characterise the rate, causes and predictors of cessation of non-vitamin K antagonist oral anticoagulants (NOACs) in patients with atrial fibrillation (AF). Patients and methods: Consecutive patients with AF with a long-term anticoagulation indication treated with NOACs (dabigatran, apixaban and rivaroxaban) in our centre from September 2010 through December 2016 were included. Prospectively collected data with baseline characteristics, causes of cessation, mean duration-to-cessation and predictors of cessation were analysed. Results: The study comprised 1415 consecutive patients with AF, of whom 439 had a CHA2 DS2 -VASc≥1 and were on a NOAC. Mean age was 71.9±8.7 years and 37% were females. Over a median follow-up of 3.6 years (IQR=2.7–5.3), 147 (33.5%) patients ceased their index-NOAC (113 switched to a different form of OAC), at a rate of 8.8 per 100 patient-years. Serious adverse events warranting NOAC cessation occurred in 28 patients (6.4%) at a rate of 1.6 events per 100 patient-years. The mean duration-to-cessation was 4.9 years (95% CI 4.6 to 5.1) and apixaban had the longest duration-to-cessation with (5.1, 95% CI 4.8 to 5.4) years, compared with dabigatran (4.6, 95% CI 4.2 to 4.9) and rivaroxaban (4.5, 95% CI 3.9 to 5.1), pairwise log-rank p=0.002 and 0.025, respectively. In multivariable analyses, age was an independent predictor of index-NOAC cessation (HR 1.03, 95% CI 1.01 to 1.05; p=0.006). Female gender (HR 2.2, 95% CI 1.04 to 4.64; p=0.04) independently predicted serious adverse events. Conclusion: In this 'real world' cohort, NOAC use is safe and well-tolerated when prescribed in an integrated care clinic. Whether apixaban is better tolerated compared with other NOACs warrants further study.